التطرف العرقي والديني دراسة مقارنة في فكر وممارسات النازية والصهيونية - المحمود, جمال; القطان, فراس (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يتناول البحث ظاهرة التطرف العرقي والديني، وما بني عليها من نظريات عنصرية أدت إلى نتائج كارثية على مستوى البشرية جمعاء، من حروب واحتلال. وإذ يدرس البحث نموذجين واضحين في التطرف العرقي والديني، هما النازية الألمانية والصهيونية، فإنه يحاول تسليط الضوء على التشابه الكبير بينهما في الفكر والممارسة. فالنازية الألمانية: تعد أن العرق الألماني متقدم على كل الأعراق، وأنه أنقى أمة بين أمم العالم أجمع، ولا يجوز اختلاطه بالآخرين، وعلى ذلك فإنه يمتلك الحق في أن يؤمن المدى والمجال الحيوي الذي يجب أن ينتشر فيه، محاولاً بذلك تبرير أحقيته في السيطرة والاستعمار. أما الصهيونية: فإن عنصريتها تتمثل بادعائها أن اليهود شعب الله المختار الذي يتفوق على غيره من الشعوب، مبرراً احتلاله وتوسعه. وبناء على ذلك يحاول الباحث الوصول إلى إستراتيجية مبنية على أسس علمية تدحض هذا الفكر العنصري والنظريات الباطلة التي روج لها، والتي تعد خطراً جسيماً يهدد مستقبل الإنسانية ويقضي على أواصر اللحمة بين الشعوب، مبيناً أن وجود هذه النظريات العنصرية ما كانت لتنشأ وتنمو لولا رعاية الاستعمار لها بهدف تبرير حروبه وغزوه بكل أشكاله وتوسعه وسيطرته على باقي بلدان العالم. The research cleans up a phenomenon of the extremism of religious and racial on the basis of detestation of racial theories arrive to disaster results on all the humanity level from wars and accupation. The research studies two distinct samples in racial they are the Zionism and German Nazist, the research tries to spot light on the big similarity between them in the practice and thoughts, the German of Nazist is considering that German racial is development on all racials, it is clearest nation between all of world nations and it shouldn’t be mixed in others. However it has right in secures on the extent and living space that should be spread in, it is trying to justification it right in domination and colonization. However the Zionism: it racism is torture in claim that Jews shold be the chosen people of Good and it successfulls on others peoples that was the justification in occupy and expand, the aim of researcher from that is trying to reach to strategic based on scientific founditions refute the racial thought that make serious danger, it threats the humanity future and annihilates on the contact bond between peoples. The research clears existence like this racial theories that don’t existe and grow except for care of colonialism to it for justification it wars and invation in all forms expansion and domination on remainder countries world.